Non-compliance, organizational deviance and useful illegality: towards a unified agenda of research - Mitra, Subrata Kumar; Pohlmann, Markus; Valarini, Elizângela (Political corruption and organizational crime, 2021)
The essays that we have brought together in this volume are intended to reassess the significance of partial compliance in public life. The conference which set the momentum for this volume had focused on illegal campaign and party financing. However, in the process of putting the papers together as an edited volume, we have expanded the scope quite radically, taking on a number of additional themes. In the event, the book takes our analysis beyond the political arena into market transactions, involving, in the cases we have examined, acts of infringement of the law. This epilogue reviews our findings and suggests the steps ahead, for future research.
Gesehen am 13.01.2022